Significant Association of miR-605 rs2043556 with Susceptibility to Breast Cancer - Kazemi, Arezu; Vallian, Sadeq (MicroRNA, 2020)
Background: MicroRNAs (miRNAs) are noncoding RNA molecules, which directly regulate gene expression. It has been documented that single nucleotide polymorphisms in miRNA genes could alter the regulation of miRNA expression and function. Objective: In this study, the allele and genotype frequency of miR-605 rs2043556 and its association with breast cancer were investigated in the Iranian population. Methods: Genotyping was performed in 162 females affected with breast cancer and 180 healthy individuals. Genotyping was performed using Restriction Fragment Length Polymorphism (RFLP) followed by Sanger sequencing. Results: The data showed the presence of Hardy Weinberg equilibrium (HWE) for this marker in the Iranian population. Allelic frequency for A and G allele was 0.75 and 0.25, respectively. Odd ratios for the association between miR-605 rs2043556 AG/GG genotypes was 3.86 with p-value= 0. Conclusion: The results indicated an increased risk for breast cancer susceptibility for miR-605 rs2043556 in the Iranian population.
Keywords: MIRN605